Controvèrsia inquisitorial al segle XVIII entorn de la pintura d'una beata estigmatitzada. - CERDÁN OP., ALFONSO ESPONERA; SASTREAL ZAMORA, MARIA-PILAR (Scripta, 2016)
In 1738, in the church of the convent at Santo Domingo at Palma, a friar offers some theological 'literal conclusions' which he dedicates to the Blessed dominican Lucía de Narni. The Propaganda Act is written on a sheet, and having been distributed, mentions the stigmata on the hands and side of the blessed. The Inquisition, influenced by the Franciscans, denounces and orders the suspension of the designated academic ceremony. The Dominicans appeal to Madrid and Rome. This is another example of women, along with other stigmatized, that were victims of the monopolistic attitude of the Franciscans. It is also an expression of the chronic confrontations between the two mendicants orders in Mallorca.